(untitled) (Bangladesh Journal of Botany, 2023)
In the present study transcriptone sequencing and RT-PCR detection of leaf sample of Commelina communis L. were investigated. A diseased leaf sample was selected for transcriptome sequencing and two contigs with lengths of 5845 and 3450 nucleotides (nt) were obtained. They were confirmed by RT-PCR with seven pairs of primers, and RNA1 and RNA2 (GenBank MZ571836 and MZ571837) were determined to be 5880 nt and 3478 nt, respectively. Homology analysis and evolutionary relationship analysis showed the highest homology with BBWV2 (MN786954 and MN786955), for 97.5 and 88.4% at the nt and amino acid (aa) levels, respectively. This is the first report of BBWV2 infection in C. communis in the world. Specific primers R2-2F/R were used to assess the association of BBWV2 with C. communis disease, and positive fragments were obtained only in the diseased plants, indicating the association of BBWV2 with the disease. Bangladesh J. Bot. 52(2): 569-574, 2023 (June) Special